PENGARUH LATIHAN MENGGUNAKAN TALI DENGAN SASARAN DAN DRILL BOLA PANTUL TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI ATLET REMAJA PBV BINA PUTRI TAHUN 2024 - Ridwan Nasution , Ahmad; Siahaan, David (JURNAL ILMU KEOLAHRAGAAN, 2024)
The purpose of this research is to determine the effect of training using a rope with a target and bouncing ball drills on the volleyball bottom passing ability of young female athletes at PBV Bina Putri Volleyball Club in 2024. Location This research was conducted at Jl. Mangan 1 LK. Vl Gg.bahagia, kel. Mabar, North Sumatra. This type of research is experimental. The population in this study were PBV Bina Putri volleyball club athletes. Sampling in this study was carried out by purposive sampling, the sample in this study was 10 people. The data collection technique used is by taking pre-test, treatment and post-test. From the data analysis that has been carried out, it is known that the hypothetical t-count value is 5.08 and t-table is 1.83, so t-count is (5.08>1.83 t-table), so there is an effect of training using a rope with a target on and bouncing ball drills on ability. PBV Bina Putri teenage athlete's volleyball underpass in 2024.